Pectic polysaccharides from the infusions of P. tridentatum, F. angustifolia and M. suaveolens: structural characterization and inflammatory influence evaluation - Martins, Vitor Manuel Ramalheira (2014)
In Tras-os-Montes region (Portugal), the small shrub (Pterospartum tridentatum) , the narrow-leafed ash (Fraxinus angustifolia), and the apple mint (Mentha suaveolens) are vegetable species frequently used in the preparation of infusions for medicinal purposes. According to the popular tradition, the infusions prepared from P. tridentatum, F. angustifolia and M. suaveolens protect against diabetes, hypertension, high levels of cholesterol and uric acid.